Phase transitions for XY-model on the Cayley tree of order three in quantum Markov chain scheme - Mukhamedov, Farrukh; Saburov, Mansoor (Elsevier, 2011)
In the present Note we study forward Quantum Markov Chains (QMC) defined on a Cayley tree. Using the tree structure of graphs, we give a construction of quantum Markov chains on the Cayley tree. By means of such constructions we prove the existence of a phase transition for the XY-model on a Cayley tree of order three in QMC scheme. By the phase transition we mean the existence of two distinct QMC for the given family of interaction operators {K_{x,y}}.